Aktivitas Ekstrak Buah Adas (Foeniculum Vulgare Mill.) terhadap Uterin Tikus Wistar Betina yang Belum Dewasa - Kurnia Agustini; Dwi Riani Wulandari; Lestari Rahayu (JURNAL ILMU KEFARMASIAN INDONESIA, 2017)
Fennel fruit (Foeniculum vulgare Mill.) is one of traditional plant medicine known having effects as anti-infl ammatory, analgesic and antioxidant. It also has been reputed to increase milk secretion, promote menstruation, facilitate birth, alleviates the symptoms of the male climacteric andincrease libido. Fennel fruit contains mainly with essential oils, such as anethole. It also contains lignan and flavonoids that are predicted having an estrogen-like eff ect or as phytoestrogen. Phytoestrogen is weak agonists for estrogen and can elicit statistic signifi cantly increases in uterine wet weight, at definite dose, in the uterothrophic bioassay. It is known that estrogen has eff ect on woman’s sexual organ, such as proliferation of uterine, mammary and ovary. The aim of this research was to investigate the estrogenic eff ect of fennel fruit’s ethanolic extract in immature, 19 days old, Wistar female rats. These models represent the climacteric/menopause phase, where estrogen level is very low because in this age, estrogen not yet produced by ovary. The testing animals were divided into fi ve groups, namely normal group, estradiol control group and three level doses of fennel extract (30 mg/200 g BW; 60 mg/200 g BW and 120 mg/200 g BW). The result indicated that start on 60 mg/200 g BW, fennel extract signifi cantly (α=0.05) increased wet weight of uterine. Fennel extract also lengthen the uterine and increased proliferation of uterine, such as uterine diameters, endometrium diameters and uterine thickness on dose 60mg/200gBW and 120mg/200gBW. Analysis of vaginal smear showed vaginal lubrication eff ect, surprisingly start on 60mg/200BW could induce estrous cycle.